Peran Kepala Madrasah dalam Meningkatkan Efektifitas Administrasi di Madrasah Ibtidaiyah - Hasibuan, Hadi Rafitra; Musthofa, Zainul; Nadhifah, Dinah (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The study entitled "The Role of Madrasah Principals in Improving Administrative Effectiveness in Madrasahs" uses a library research method by reviewing various scientific literature, academic journals, and previous research results. The purpose of this study is to analyze and understand the strategic role of madrasah principals in improving the administrative effectiveness of Islamic educational institutions. Based on the results of the literature review, it was found that the effectiveness of madrasah administration is largely determined by the ability of the madrasah principal to carry out leadership, management, supervision, and oversight functions in an integrated manner. Madrasah principals play a vital role in planning, organizing, and controlling all administrative activities, from curriculum administration, student affairs, personnel, to finance and infrastructure. The research findings indicate that strategies to improve administrative effectiveness can be implemented through strengthening administrative planning, optimizing communication and coordination, utilizing information technology, and developing human resource competencies. In addition, madrasah principals with Islamic personalities are able to integrate the values ​​of honesty, responsibility, and trustworthiness throughout the administrative system, thereby creating a religious and productive work climate. Transformational and spiritual-integrative leadership models have been proven effective in improving administrative performance in madrasas. The study's conclusions confirm that administrative effectiveness depends not only on an organized system but also on the leadership quality of the madrasah principal, who is able to combine managerial professionalism with Islamic spiritual values. This research contributes theoretically to the development of Islamic education management and offers practical implications for strengthening effective, transparent, and religiously imbued madrasah administrative governance.